Performance analysis of equivalent-circuit topologies for periodic leaky-wave antenna rsymmetric Radiators - Hernández Escolar, Alberto; Abdo-Sánchez, María Elena; Mateos-Ruiz, Pablo; Esteban Marzo, Jaime; Martín-Guerrero, Teresa María; Camacho-Peñalosa, Carlos (My University, 2022)
The traditional problem of broadside radiation degradation in leaky-wave antennas has been overcome in the past years with the introduction of some asymmetry in the radiator. This article analyses the performance of two equivalent-circuit topologies, previously proposed in the literature for asymmetric structures. The aim is to shed some light on the choice of the appropriate circuit when selecting the degree of asymmetry in the unit-cell of periodic leaky-wave antennas. The comparison is carried out through the extraction of the circuit parameters of three different structures and each of them with different degrees of asymmetry.
Keywords: Circuitos electrónicos - Diseño; Antenas - Diseño y construcción; Electromagnetismo; Ondas de fuga; Circuito Equivalente; Autovalores; Antena de Onda Progresiva